Gambaran Makroskopik dan Mikroskopik Pankreatitis Kronis dalam Pemeriksaan Postmortem - Djai Yen Liauw; Vionita Simanjuntak; Lura Maharani; Clara Widjaja; Patricia Amanda Widjaja; Tirza Amelia SH; Jacinda Phowen; Gabriela Geby Wisal; Bernaditha Feby Shela Siburian; Nadya Calista Kimberly; Ireina Karyn; Vera Olivia (Jurnal MedScientiae, 2023)
Pancreatitis is a disease of the pancreas due to an inflammatory process. Chronic pancreatitis often causes complications that increase both morbidity and mortality. Postmortem examination can provide macroscopic and microscopic findings that allow to determine the etiology of chronic pancreatitis. This article aims to comprehensively understand the macroscopic and microscopic features of chronic pancreatitis in the postmortem context, as well as identify the relevant implications of the findings. This article is a literature review research with database sources from PubMed, Google Scholar, ProQuest, and EBSCO research databases. Fibroinflammatory changes and ductal dilation (corkscrew appearance) are the macroscopic features of chronic pancreatitis, while microscopic changes can be found as loss of asinus, ductal dilation, and chronic inflammatory infiltrates. These findings can detect the underlying diseases of chronic pancreatitis due to excessive alcohol consumption or genetic disorders, and it has important forensic implications, such as genetic counseling or assessment of alcohol use that has the potential to contribute on death. In conclusion, chronic pancreatitis can be identified through macroscopic and microscopic findings on postmortem examination, and the findings have important implications in determining the cause of death and understanding the underlying disease condition.